REPRESENTASI EKOLEKSIKON DALAM TEMBANG SEKAR RARÉ DAN EKSISTENSINYA DI LINGKUNGAN ANAK-ANAK - A.A. Pt. Suari (Subasita: Jurnal Sastra Agama dan Pendidikan Bahasa Bali, 2022)
Sekar Raré is Balinese game folksongs for children. This paper discusses the forms of lexicons related to ecology in Sekar Raré folksongs. The object of this qualitative descriptive study is the text of Balinese kid’s folksongs which are grouped into three types, namely dolanan, gending jangér, and gending Sang Hyang. The data collection grouped and interpreted using the perspective of ecolinguistic theory. The results showed that the ecolexicon in Sekar Raré folksongs are (1) flora lexicons (tunjung, dapdap, poh,…) and fauna lexicons (meong, goak, bé,…); (2) derivative word forms (padi, mamula, durén-durén,…); (3) onomatopoeia (kung kék kék kung kék kong); and (4) nouns (dongkang), adjectives (miik), verbs (mencar). 50.4% of students grade 7 until 9 no longer sing Sekar Raré and only 49.5% of students still sing the songs for certain activities. Students are familiar with ecolexicons such as semut api, mencar, dungki, waluh, and alang-alang. However, while just a few are familiar with the sesapi putih, sowane, katilampo nguda, nunun, and pudak.Keywords: Balinese, Sekar Raré, Ecolinguistics